Family Functioning Predicts Body Mass Index and Biochemical Levels of Youths with Nonalcoholic Fatty Liver Disease. Issue 2 (February 2017) - Smith, Justin D.; Montaño, Zorash; Maynard, Andrew; Miloh, Tamir
ABSTRACT: N/A: Family functioning is associated with obesity-related chronic illnesses and impedes effective treatment of weight-related conditions, such as nonalcoholic fatty liver disease (NAFLD). Objectives: Evaluate the utility of a brief screening measure of family functioning among youth aged 8 to 18 years being treated in a specialty care clinic for NAFLD. Methods: Thirty-nine youths and their caregivers participated. Relations between family functioning and anthropometric and biochemical variables assessed 3 to 6 months later were evaluated using regression analyses, controlling for child age, gender, and ethnicity. Results: Family functioning was related to significantly higher body mass index (BMI) and levels of cholesterol, HbA1c, and glucose, but not serum alanine aminotransferase (ALT)—a marker of NAFLD—controlling for baseline levels. The magnitudes of effects were medium for models of BMI (Cohen's f 2 = 0.29), cholesterol (0.32), and blood glucose (0.30) and small to medium for HbA1c (0.23) and ALT (0.10). Conclusion: This is the first study to examine the role of family functioning in youth with NALFD. Treatment programs might consider screening for family functioning to identify families that could benefit from a family-centered behavioral intervention.